Dynamics production of corn and beans in Mexico from 1980 to 2014 - De los Santos Ramos, Mauricio; Romero Rosales, Teolincacihuatl; Bobadilla Soto, Encarnación Ernesto (Agronomía Mesoamericana, 2017)
The objective of this work was to evaluate the dynamic of corn and bean production in Mexico. Retrospective analysis was conducted in order to identify critic points, changes and adjustments given in the sector, as a result of Mexican government policies. Data was obtained from SAGARPA, Bank of Mexico, Secretary of Economy and Food and Agriculture Organization. Indicators were evaluated, as annual average growth rate (TCMA) and growing indicators, trends and real prices were evaluated. When doing the analysis, it was considered as a variable the country as a whole. The data of plantings, production, prices and imports of corn and beans in Mexico between 1980 and 2014 was analyzed. The plantings of corn and beans showed a decrease of 1.8 million and 193 thousand hectares respectively, the performance of corn increased on 1.47 t/ha and for beans, and 160 kg/ha for corn production and had a TCMA of 1.8% equivalent to 10.1 million tons, and beans had a TCMA of 0.89% with an increase of 338 783 t. Corn and beans, at constant prices, had a decrease of 64.6% and 59.0%, the decreased was of 441.9 and 976.3 dollars per ton respectively. The imports of corn had a TCMA of 2.84% ending 2012 with 9.5 million tons, the imports of beans don’t show any trend. The critic point of imports began with the North American Free Trade Agreement, where Mexico changed from a close economy to an open one, in which the government stimulates more imports, than national production.